(untitled) (ALPHA. Journal of Arts, Literature and Philosophy, 2016)
In this paper, we examine whether knowledge of our own human intimacy is natural or exclusively supernatural, as Kierkegaard proposes. We conclude that, even though this idea is not explicit in his writings, he admits that man’s relationship with God is exclusively supernatural through faith, and that faith is not cognitive because it accepts that God is behind the absurd; hence, philosophical anthropology is not possible as a science.